A comparative study on the tax and fee reduction policies for sustainable development: Empirical analysis from the world’s three major economies in tackling COVID-19 - Yujuan, Ma; Guangli, Yang; Bo, Li (Frontiers in Environmental Science, 2022)
The global COVID-19 epidemic in 2020 has caused a significant drop in many countries' employment rates and economies. Numerous countries have implemented a number of tax and fee reduction policies in response to the COVID-19 epidemic. This essay analyzes the tax and fee policies and results of the three largest economies in the world—China, the United States, and Japan—in response to COVID-19. We will first compare the effects of tax and fee reduction policies horizontally across China, the US, and Japan. The second step is comparing the impact of tax and fee reduction policies. According to the study, in response to COVID-19, China, the United States, and Japan each implemented separate tax and fee policies. The United States primarily offers corporate income tax, personal income tax relief, and increased social welfare and subsidies; Japan primarily offers income tax, consumption tax, and business tax relief. China primarily offers tax relief for VAT, corporate income tax, and social security funds. Therefore, each country should develop tailored tax and fee reduction policies in response to COVID-19 or major emergencies in order to support economic growth and employment. Last but not least, the following policy suggestions are made for China to deepen its tax and fee reduction policy further: broaden the tax base, raise fiscal revenue; innovate its tax reduction policy based on the country's current anti-epidemic tax reduction policy; and organically combine tax and fee reduction with furthering the country's fiscal and taxation system reform. The creation of tax reduction policies in response to significant emergencies will benefit in specific ways from the findings of this study.